Public health engagement: new opportunities and challenges in 60 years of China’s health aid to Africa - Junfang Xu; Liangmin Gao (BMJ Global Health, 2023)
Along with China’s active engagement in global affairs over the past decade, China’s public health engagement (CPHE) has become an essential element of China’s 60th anniversary of health aid and cooperation with Africa. Through analysis, we found that CPHE in Africa reflects a new shift in the content and form of China’s foreign health aid. Compared with China’s medical teams which only involve bilateral cooperation, CPHE has a number of substantive characteristics, mainly including the construction of public health infrastructure, malaria control, participation in public health emergencies and the provision of global public goods. This complexity necessitates that CPHE be implemented in a different form from China’s medical teams, by adopting inclusive multiparty cooperation involving African and international partners. However, CPHE in Africa still faces a number of challenges in its practices. In particular, these challenges arise from the cross-cultural practice process, the African sociocultural context, the experience of public health and its participants. While the reasons for these challenges are diverse, this study argues that the main reason is the lack of multidisciplinary engagement in the Africanisation of the Chinese experience that corresponds to cross-cultural practice. On the Chinese side, a systematic strategy is needed to critically refine these challenges.